(untitled) (Kinesiology, 2021)
The aim of this study was to provide a retrospective overview of injuries during one basketball season and to analyse injury rates and potential risks among professional male and female basketball players in the First Croatian National league. A hundred and forty-two (89 males and 53 females) of 223 basketball players (64%) sustained an injury during the previous season. Body height, total game exposure and total on-court time per game (p<.05) were the identified risk factors for females, while the number of training hours per week was found to be a risk factor for males (p<.05). The highest proportion of injured players was found among centers for men (74%) and forwards (70%) for women. Forty-three percent of injuries were moderately serious, 31% were minor, and 20% serious injuries. Majority (80%) of all injuries were to the lower extremities and men sustained fewer lower extremity injuries compared to women (IRR=0.88 95% CI=0.6 to 1.3). Ankles were the most prevalent injury site for both men and women followed by the knee. Men sustained significantly fewer knee injuries compared to female athletes (IRR=0.44 95% CI=0.17 to 1.11). The most common injury type was ligament injuries (31%), followed by muscle tears/strains (20%). Game incidence injury rate for males was significantly lower than for females (IRR=0.55, p=0.01 [95% CI=0.34-0.89]). Those athletes who, on average, played more than 20 minutes in games were almost twice more exposed to an injury (OR=2.09, 95%CI=1.17,3.72). This is the first descriptive epidemiological study estimating rates and risks of injuries among the Croatian professional basketball players. Key words: professional players, injury rates, risk factors, prevention